SIFAT EKSTRAK KULIT ACACIA DECURRENS SEBAGAI INSEKTISIDA (Antitermitic Properties from: Acacia decuerena ,Bark ExtractilHIB) - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1990)
creening triala were cond.ucted  to determine.  t~, antitermitic properties. of methanol:dieth.yl ether:ethyl acetate (M:D:E) and acetone:diethylether:ethyl   acetate (A:Dfg)   tannin extract obtained from Acaciadeeurrens bark. The eoa- centration for eaolt>treatmentare 0,10 and'0,14  g/ml, and Cryptotennes  cynocephalus Light termite were uaed to evaluate antiter:miticproperties.TM rault  ahowa that complete termite mortality occured on methanol:diethyt ether:ethyl acetate. Nearly Complete mortality occurred on acetone:diethyl:ethyl  ether:ethyl acetate and the filtrat from each  soluent is also still toxic.i